Catastrophic Maternal Complications of Morbidly Adherent Placenta in Patients with History of Previous Caesarean Delivery (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Objective:The study is aimed to describe the grave maternal outcomes encountered inpatients having morbidly adherent placenta along with history of previous caesarean section.Materials and Methods: This was a cross-sectional study from September 2014 to August2015. All the patients attended in the in-patient department of obstetrics & gynaecology inDMCH during the study period having morbid adhesion of placenta (diagnosed antenatallyby USG or diagnosed preoperatively) along with history of previous caesarean section.Result: Total 10,805 obstetric patients delivered during the study period, of which 6,337patients had caesarean sections. Out of them 37 pregnant patients were found to havemorbid adhesion of placenta along with history of previous C/S. The incidence is 1 in 292deliveries. All of the 37 patients needed hysterectomy for intractable per operativehaemorrhage. All the patients needed transfusion of more than 04 units of blood. Nineteenpatients needed ICU supports Ten (27%) patients died. Other grave complications werehypovolemic shock (19 patients), bladder injury (16patients), renal failure (07 patients),multiorgan failure (07 patients) and DIC (06 patients).Conclusion: All the patients of morbidity adherant placenta with previous Caesarean Sectionneeded caesarian hysterectomy and ten patients died.Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 96-100